Sodium Zirconium Cyclosilicate in the Therapeutic Management of Hyperkalemia: A Systematic Review of Efficacy and Safety - Zavaleta Monestel, Esteban (2026)
Objective: The objective of this study is to evaluate the efficacy and safety of sodium zirconium cyclosilicate in the treatment of hyperkalemia in adult patients based on the available scientific evidence. Methods: A systematic review of randomized controlled trials evaluating SZC in adult patients with hyperkalemia was conducted, including populations with chronic kidney disease and heart failure and patients undergoing hemodialysis. Outcomes assessed included serum potassium reduction, achievement and maintenance of normokalaemia, and adverse events. Results: Seven randomized controlled trials were included. SZC produced a rapid and significant reduction in serum potassium, with reductions of up to 1.28 mmol/L within 48 h and onset of action observed as early as 1–4 h. Across studies, 63–92% of patients achieved normokalaemia within 24–48 h, and maintenance therapy sustained normokalaemia for up to 28 days and longer in selected populations. The most frequently reported adverse events were mild-to-moderate edema and constipation, while hypokalemia was infrequent (<5% in most studies). Conclusions: Sodium zirconium cyclosilicate is an effective and generally well-tolerated option for the management of hyperkalemia, providing rapid potassium reduction and sustained normokalaemia. However, no randomized controlled trial included in this review demonstrated a significant benefit of SZC over comparators in major clinical outcomes—hospitalizations, cardiovascular events, or mortality; the evidence of clinical benefit is therefore absent from the current randomized trial literature.